Negative-Pressure Therapy to Reduce the Risk of Wound Infection Following Diverting Loop Ileostomy Reversal: An Initial Study. (March 2016) - Cantero, Ramon; Rubio-Perez, Ines; Leon, Miguel; Alvarez, Mario; Diaz, Beatriz; Herrera, Ana; Diaz-Dominguez, Joaquin; Rodriguez-Montes, Jose Antonio
ABSTRACT: OBJECTIVE: To evaluate if the application of a negative-pressure therapy system (Prevena Incision Management System, Kinetics Concepts Inc, [KCI] an Acelity Company, San Antonio, Texas) on ileostomy-closure surgical wounds would reduce surgical site infections (SSIs) in comparison with conventional closure and dressing. DESIGN: Prospective interventional pilot study. SETTING: La Paz University Hospital, tertiary care academic hospital in Madrid, Spain. PATIENTS: The Prevena device was applied on the wounds of 17 consecutive patients undergoing ileostomy reversal. Control subjects were 43 patients undergoing the same procedure, in which conventional dressings were used for the wound. INTERVENTION: The device was applied on the wound immediately after surgery (under sterile conditions) and maintained for 5 to 7 days. Patients were evaluated daily, and on the seventh postoperative day, the device was removed and wounds carefully inspected. Another evaluation was performed a month after the surgical intervention in the outpatient clinic. MAIN OUTCOME MEASURE: The primary end point of the study was the detection of SSI (defined according to the Centers for Disease Control and Prevention definitions). Other intervention-related complications were also registered. MAIN RESULTS: There were no significant differences in demographic variables between groups. In the control group, 9 patients (21%) presented SSI, with statistical significance ( P < .038) when compared with the intervention group (0%). There were no complications associated with the application of the Prevena device. Other complications (for example, ileus or obstruction) occurred in 30% of patients. CONCLUSIONS: The negative-pressure Prevena System was safe and easy to use and may prevent SSIs in dirty wounds, such as those from ileostomy closure.